1999
DOI: 10.1097/00007890-199908270-00016
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Postoperative Infections Associated With Peritoneal Dialysis in Renal Transplant Recipients

Abstract: Renal replacement therapy with PD immediately before transplantation negatively affects outcome as compared with HD, predisposing patients to a greater incidence of postoperative infections and rejection and a longer hospital stay. Further study in a randomized controlled trial may help determine how adjustment of the dialysis method can optimize transplantation outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 11 publications
2
37
3
1
Order By: Relevance
“…Infective complications and patient mortality have been reported to be higher with PD [18, 19]. In contrast, some studies have reported fewer bacterial and hepatitis infections in PD patients after transplantation, and a similar rate of other infections in HD and PD patients [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Infective complications and patient mortality have been reported to be higher with PD [18, 19]. In contrast, some studies have reported fewer bacterial and hepatitis infections in PD patients after transplantation, and a similar rate of other infections in HD and PD patients [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Snyder et al [9] in a study of 22,776 patients suggested that PD patients had a higher risk of graft failure than HD patients during the first 3 months after transplantation with an adjusted OR 1.23 (95% CI 1.09-1.39). These results could be explained by a higher incidence of infections and early graft thrombosis in PD patients [33][34][35][36] . Typically, PD patients have a better immunologic state, which could have an adverse effect on the outcome of graft survival [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Im Gegensatz zu den Calcineurininhibitoren inhibiert es dann mTOR, das eine wichtige Rolle bei der intrazellulären Übermittlung der IL-2-Wirkung am IL-2-Rezeptor spielt [12,13] [14]), den Ernährungszustand, begleitende Virusinfekte oder Reaktivierung von Krankheitserregern einer latenten Infektion beeinflusst [15,16,17].…”
Section: Sirolimusunclassified